Zalaegerszeg és testvérvárosai - Kránicz, Judit (Közép-Európai Közlemények, 2010)
During the past centuries many great philosophers and statesmen dreamt about the possible constitutional scope of exceeding Europe’s political division and fulfilling the unified/united Europe. Most conceptions outlined the practical realization at a supranational level, although in the last decades there has been a greater emphasis on the sub-national (regional, micro-regional) level or else the “multi-level” Europe. Considering its scientific importance there has been less mention of the importance of the local, regional networks, however, their functionality –in the form of sister town connections –has been experienced by many towns in Hungary. In my thesis I intended to shed light on the fact that the sistertown connections –if being able to overstep the mayors and the local authorities’ protocol meetings -and it can be the pledge of their viability, take a prominent part in framing the “bottom up” Europe. The personal, civil relationships, the common interests and the solutions to collective problems may all lead to a continuity in the increasingly “multigeared” European integration. In order to present the subject matter I selected the analysis of sister town connections related to the county town, Zalaegerszeg. My research questions were as follows: to what extent the sister town connection of Zalaegerszeg has changed in terms of geographical and content orientation, what elements of networking, independent from any political orientation, have been used, how the intensity fluctuation of the connections can be explained. The conclusion of my research is that the citizens, the civil organisations and the local authority of Zalaegerszeg, whose number of sister towns –fourteen –is greater than the Hungarian average, build their sister town connections in a conscious way, meanwhile integrating them functionally and successfully at a local level into the network of international connections.